2014
DOI: 10.15442/apgr.19.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of bisphenol A and its effects on the human body

Abstract: Bisphenol A (BPA) is a key component of polycarbonate plastics and epoxy resins, which are widely used for production of food storage containers and numerous other products, including contact lenses, protective glasses, infant incubators, CDs and DVDs. Moreover, BPA is an additive in the production of dental composites, paints, fungicidal and inflammability reducing agents. Bisphenol A primarily gets to the human body from food products kept in BPA containers. The other important sources of BPA are thermal pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
8
2
Order By: Relevance
“…Variable BPA contamination levels may be detected in raw, commercial milk and cheese. Bibliographic data reported higher BPA levels in commercial milk (0.38-5.47 μg/kg, and 14.0-521.0 μg/kg) and cheese (2.24 μg/kg) (Molina-Garcìa et al , 2012; Grumetto et al , 2013 ; Wlodarczyk, 2015 ) than those detected in our study in raw milk. The different contamination levels in raw, commercial milk and cheese could be related to factors, such as the quality of the materials in contact with milk during production at the farm, and the treatment conditions and packaging materials used at the dairy company (Liu et al , 2008 ; Grumetto et al , 2013 ).…”
Section: Discussioncontrasting
confidence: 47%
“…Variable BPA contamination levels may be detected in raw, commercial milk and cheese. Bibliographic data reported higher BPA levels in commercial milk (0.38-5.47 μg/kg, and 14.0-521.0 μg/kg) and cheese (2.24 μg/kg) (Molina-Garcìa et al , 2012; Grumetto et al , 2013 ; Wlodarczyk, 2015 ) than those detected in our study in raw milk. The different contamination levels in raw, commercial milk and cheese could be related to factors, such as the quality of the materials in contact with milk during production at the farm, and the treatment conditions and packaging materials used at the dairy company (Liu et al , 2008 ; Grumetto et al , 2013 ).…”
Section: Discussioncontrasting
confidence: 47%
“…The presence of BPA in dairy products is not surprising since previous studies indicated the presence of BPA in raw milk samples at 1.3-2.4 ng/g in Iran (Sadeghi vd., 2016) and 0.035-2.776 µg/L in Italy (Santonicola vd., 2019) and even at levels up to 521.0 μg/L in commercial milk samples (Grumetto vd., 2013). For comparison purposes, higher concentration of BPA has been found in other foods of animal origin including in egg (133 ng/g) (Liao and Kannan, 2013) and not canned meat (13 μg/kg) (Bemrah vd., 2014), yet somewhat lower in quantified in meat (0.48 μg/kg), poultry liver pate (0.48 μg/kg) and butter (0.56 μg/kg) (Wlodarczyk, 2015). Noticeable differences in the concentration of BPA were observed among cheese types and samples in the current study.…”
Section: Resultscontrasting
confidence: 45%
“…We are not aware of any similar study on BPA in raw cow milk. Most studies have reported BPA levels only in commercial milk (from 14.0 to 521.0 µg/L) or cheese (2.24 µg/kg; Grumetto et al, 2013;Wlodarczyk, 2015;Mercogliano and Santonicola, 2018). If we compare our data with contamination levels of commercial milk, the latter are generally higher.…”
Section: Hot Topicmentioning
confidence: 67%
“…These differences between raw and commercial milk could be related to different factors, such as the quality of the materials in contact with milk during manufacturing and the treatment conditions at the dairy company (e.g., thermal treatments, packaging; Grumetto et al, 2013). The BPA concentrations quantified in raw milk were high compared with those in principal foodstuffs of animal origin, such as meat (0.48 µg/kg), poultry liver pate (0.48 µg/kg), and butter (0.56 µg/kg), but lower than those detected in sea fish (0.89 µg/kg), eggs (<2-2.4 µg/kg), and fats (<4 µg/kg; Wlodarczyk, 2015).…”
Section: Hot Topicmentioning
confidence: 80%